Characterizing the Impact of Facial Rehabilitation on Acute Facial Paralysis - Abend, Audrey; Perillo, Lauren; DeSimone, Jenna; Eytan, Danielle F. (Facial Plastic Surgery, 2024)
Evidence on facial rehabilitation therapy (FRT) for acute facial paralysis (FP) remains limited. We present a retrospective review of patients with acute FP who have received FRT with physical therapists within 1 year of FP onset as determined by Sunnybrook Facial Grading Scale (SFGS) composite scores. A total of 702 patients with a clinical diagnosis of FP were referred to a university rehabilitation program between January 1, 2015 and January 1, 2022. Seventy-six patients met the criteria, defined as FP diagnosis <12 months before FRT initiation, ≥3 therapy sessions, and sufficient follow-up data. Average number of treatment sessions between SFGS scores was 7.7. History of cancer, sex, number of treatment sessions, and initial SFGS score were correlated with change in SFGS. Time to treatment was not correlated with change in SFGS score. SFGS improved with each additional treatment session (p < 0.01). Each additional point in the initial SFGS was correlated with less change in the final SFGS score (p < 0.01). FRT can provide meaningful improvement in functionality for patients with acute FP, regardless of time to treatment. Furthermore, patients who present with poorer functionality at baseline and those who undergo more treatment are most likely to see SFGS improvement. Research comparing the effect of facial rehabilitation with other treatment modalities and to a control cohort is warranted.
Keywords: facial paralysis; facial rehabilitation; Bell's palsy; Sunnybrook facial; grading system; facial palsy